2016
DOI: 10.1016/j.jid.2016.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of TNF-α– and IL-17A–Mediated Synergistic Induction of DEFB4 Gene Expression in Human Keratinocytes through IκBζ

Abstract: Human β-defensin 2 (hBD2), encoded by the DEFB4 gene, is an antimicrobial peptide playing an essential role in inflammatory processes in the skin. hBD2 expression is regulated synergistically by tumor necrosis factor-α (TNF-α) and IL-17A; however, the underlying regulatory mechanisms are unknown. The purpose of this study was to characterize the molecular mechanism by which TNF-α and IL-17A synergistically induce hBD2 expression. In cultured human keratinocytes we show that a constitutive noninducible binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 37 publications
3
31
0
1
Order By: Relevance
“…Silencing of the DEFB4 gene in psoriasis‐reconstructed skin tissues resulted in a significant decrease in hBD2 expression, but also of the 4 investigated psoriasis disease markers, that is elafin, involucrin, K16 and Ki‐67. The silencing of DEFB4 is extremely powerful, as it is able to counteract the hBD2 induction by pro‐inflammatory cytokines present in the medium, that is, TNF‐α and IL‐17A . As such, our results confirm once more the therapeutic potential of targeting hBD2 in the treatment of psoriasis .…”
Section: Discussionsupporting
confidence: 76%
“…Silencing of the DEFB4 gene in psoriasis‐reconstructed skin tissues resulted in a significant decrease in hBD2 expression, but also of the 4 investigated psoriasis disease markers, that is elafin, involucrin, K16 and Ki‐67. The silencing of DEFB4 is extremely powerful, as it is able to counteract the hBD2 induction by pro‐inflammatory cytokines present in the medium, that is, TNF‐α and IL‐17A . As such, our results confirm once more the therapeutic potential of targeting hBD2 in the treatment of psoriasis .…”
Section: Discussionsupporting
confidence: 76%
“…IκBζ is a transcriptional co‐factor for NF‐κB and a key protein for IL‐17A–driven effects in psoriasis . To characterize the molecular mechanisms involved in the effects of dsRNA/IL‐17A, we examined the expression of IκBζ.…”
Section: Resultsmentioning
confidence: 99%
“…IκBζ is a known partner of NF‐κB that regulates several factors involved in host defense and is implicated as a critical player in the pathogenesis of psoriasis . Previous studies revealed a NF‐κB binding site (−286/−274 nt) in IL‐36γ promoter .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we presented IκBζ as a key regulator in the development of psoriasis by identifying IκBζ as an activator of IL‐17A/TNFα‐ and IL‐17F/TNFα‐inducible psoriasis‐associated genes and proteins …”
Section: Introductionmentioning
confidence: 99%